Implementasi Kebijakan Tentang Pedoman Penerapan Sistem Informasi Kearsipan Dinamis Terintegrasi Dalam Upaya Pengelolaan Naskah Dinas Elektronik Di Sekretariat Daerah Kota Bekasi - Iqbal, Muhammad; Daraba, Dahyar; Indrayani, Etin (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2024)
An integrated dynamic archiving information system aimed at managing electronic official documents within the Bekasi City Regional Secretariat was established in accordance with Bekasi Mayor Regulation Number 54 of 2023, which outlines the Guidelines for the Implementation of an Integrated Dynamic Archiving Information System for the Management of Electronic Official Documents in the Bekasi City Government. Management of Electronic Official Documents at the Bekasi City Regional Secretariat is carried out by all Office Holders and Policy Implementers within the Bekasi City Regional Secretariat. The reality that appears in the field is that there are still apparatus and office holders who do not understand the regulation massively, manual culture is still a pattern in the management of official documents, the standardization of the policy has not been determined so that it can be said that its implementation has not gone well. Therefore, the author wants to explore this topic further. This study uses descriptive using a qualitative approach. Data collection techniques include interviews, observations, and documentation. Data analysis methods consist of data reduction, data presentation, and drawing conclusions. The study findings show that the Implementation of the Policy on Guidelines for the Implementation of Integrated Dynamic Archiving Information Systems in the Efforts to Manage Electronic Official Manuscripts at the Bekasi City Regional Secretariat is not yet optimal, however, the author suggests that the solution that needs to be considered is Substantive Socialization to Officials and Implementers, Increasing the Capacity of Apparatus and Preparation of Standard Operating Procedures. In the future, it is hoped that this policy can be implemented in accordance with the provisions that apply to all Officials and Policy Implementers at the Bekasi City Regional Secretariat.